2016
DOI: 10.14740/cr465w
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Calcium-Phosphorus Product With the Severity of Cardiac Valves Failure in Patients Under Chronic Hemodialysis

Abstract: BackgroundRecent studies have mainly focused on the roles of serum calcium and phosphorus product in the development of valvular heart failure. We determined the association of calcium-phosphorus product with the severity of heart valve failure in patients under chronic hemodialysis (being under hemodialysis for 6 months or more) in Boo-Ali Hospital in 2012 and 2013.MethodsIt was a cross-sectional, descriptive, comparative study. Thirty-three patients undergoing chronic hemodialysis were recruited to the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In humans, CKD is associated with cardiovascular disease, in particular atherosclerosis and vascular calcification, mineral and bone disorder, fractures and high risk of mortality (especially cardiovascular mortality) [ 23 , 25 , 26 , 27 ]. In human patients, high levels of sCaPP and high phosphate levels may lead to secondary hyperparathyroidism and are associated with calcification of softs tissues [ 28 ]. It is possible that in our cases, high levels of sCaPP may be associated with mineralization in other sites than kidneys (such as stomach, myocardium, lung and liver), as reported in patient with CKD [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, CKD is associated with cardiovascular disease, in particular atherosclerosis and vascular calcification, mineral and bone disorder, fractures and high risk of mortality (especially cardiovascular mortality) [ 23 , 25 , 26 , 27 ]. In human patients, high levels of sCaPP and high phosphate levels may lead to secondary hyperparathyroidism and are associated with calcification of softs tissues [ 28 ]. It is possible that in our cases, high levels of sCaPP may be associated with mineralization in other sites than kidneys (such as stomach, myocardium, lung and liver), as reported in patient with CKD [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have contended that previous relevant guidelines can be set aside and that target phosphorus levels should be set to within the normal range [25]. Therefore, physicians have tried to reduce phosphate imbalance and maintain PTH levels within the target range, to reduce CKD-accelerated cardiovascular calcification [18,23,26].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our study also found that cardiac VC was a predictive factor in both the death and compound outcome models. The study found that the prevalence of aortic and mitral valve VC in MHD patients was eight times higher than that in the general population [26][27][28] . In All rights reserved.…”
Section: .Discussionmentioning
confidence: 77%
“…Interestingly, our study also found that cardiac VC was a predictive factor in both the death and compound outcome models. The study found that the prevalence of aortic and mitral valve VC in MHD patients was eight times higher than that in the general population [2628] . In patients receiving MHD, hyperphosphatemia, hyperparathyroidism, increased fibroblast growth factor-23, and decreased co-receptor klotho levels are significantly associated with VC [27] .…”
Section: Discussionmentioning
confidence: 99%